Prevalence of high, medium and low-risk medical conditions for pneumococcal vaccination in Catalonian middle-aged and older adults: a population-based study - O. Ochoa-Gondar; I. Hospital; A. Vila-Corcoles; M. Aragon; M. Jariod; C. de Diego; E. Satue; EPIVAC Study Group (BMC, 2017)
Abstract Background Updated population-based data on the frequency and distribution of risk factors for pneumococcal disease is scarce. This study investigated the prevalence of distinct comorbidities and underlying risk conditions related to an increasing risk of pneumococcal disease among Catalonian middle-aged and older adults. Methods Cross-sectional population-based study including 2,033,465 individuals aged 50 years or older registered at 01/01/2015 in the Catalonian Health Institute (Catalonia, Spain). The clinical research database of the Information System for the Development of Research in Primary Care (SIDIAP database) was used to identify high-risk (asplenia and/or immunocompromising conditions) and other increased-risk conditions (chronic pulmonary, cardiac or liver disease, diabetes mellitus, alcoholism and/or smoking) among study subjects. Results Globally, 980,310 (48.2%) of the 2,033,465 study population had at least one risk condition of suffering pneumococcal disease (55.4% in men vs 42.0% in women, p < 0.001; 41.7% in people 50-64 years vs 54.7% in persons 65 years or older, p < 0.001). An amount of 176,600 individuals (8.7%) had high-risk conditions (basically immunocompromising conditions). On the other hand, 803,710 persons (39.5%) had one or more other risk conditions. In fact, 212,255 (10.4%) had chronic pulmonary diseases, 248,377 (12.2%) cardiac disease, 41,734 (2.1%) liver disease, 341,535 (16.8%) diabetes mellitus, 58,781 (2.9%) alcoholism and 317,558 (15.6%) were smokers. Conclusion In our setting, approximately 50 % of overall persons 50 years or older may be considered at-risk population for pneumococcal disease (almost 10 % have high-risk conditions and 40 % have other risk conditions).